Contraceptive Knowledge, Attitudes, and Practices in Algeria: A Multi-Methods Study with Women Living in Urban and Rural Areas - Chengane, Sabrine (Université d'Ottawa | University of Ottawa, 2026)
Contraception plays a crucial role in enhancing women’s health and well-being, advancing educational and career goals, improving quality of life, and contributing to a country’s social and economic development. Therefore, equitable access to contraceptive services is essential for both population health and societal development. Family planning in Algeria has long been a national priority, and the country has made significant progress contributing to increased contraceptive use over the years. However, despite these gains, recent years have seen a decline in use and a rise in unmet needs. Contraceptive behaviour, meanwhile, is shaped by various factors including individual knowledge, individual and collective attitudes, sociocultural norms, and health system-related barriers. Prevailing sociocultural norms can also render the needs of some groups invisible, leaving them underserved. Understanding lived experiences, perspectives, and contraceptive behaviours of women is essential to creating inclusive, equitable reproductive health policies and services. This thesis aims to understand the contraceptive knowledge, attitudes, and practices of women of reproductive age and to explore the contraceptive landscape in Algeria, with a focus on the facilitators and barriers to equitable access to contraceptive services. Using an action research approach, this multi-methods qualitative study is comprised of four components: a scoping review on women’s knowledge, attitudes, and practices in three Maghrib countries, in-depth interviews with women of reproductive age, interviews with key informants, and an online survey with female university students in Algeria. The findings from this research provide evidence regarding the current status of contraceptive knowledge, attitudes, and practices in Algeria, highlight the needs of underserved groups in accessing contraceptive information and service, and have the potential to inform ongoing policy and programmatic efforts.
Keywords: Contraception; Algeria; Family Planning; Sexual and Reproductive Health (SRH); Women’s Health; Health System; Service Access; Knowledge, Attitudes, Practices; KAP